2011
DOI: 10.3389/fneur.2011.00039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrical Passive Cycling on Spasticity in War Veterans with Spinal Cord Injury

Abstract: Introduction: Muscle atrophy, spasticity, and deformity are among long term complication of spinal cord injury (SCI) veterans. There are numerous studies evaluating effect of functional electrical stimulation on muscle properties of SCI people, but less research has focused on the benefits of passive cycling in the management of spasticity and improving ROM of lower limbs in individuals with SCI. Aims: To evaluate the effect of electrical passive cycling on passive range of movement spasticity and electrodiagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 27 publications
0
41
0
5
Order By: Relevance
“…In the present study, FES cycling led to a decrease in spasticity, which was consistent with previous studies. 17,21,22 Increase in muscle strength may allow to counteract spasticity in a more effective manner. FES-induced neural activity may change the balance of excitation in favor of inhibition in spinal cord by inducing neuroanatomical plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, FES cycling led to a decrease in spasticity, which was consistent with previous studies. 17,21,22 Increase in muscle strength may allow to counteract spasticity in a more effective manner. FES-induced neural activity may change the balance of excitation in favor of inhibition in spinal cord by inducing neuroanatomical plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, exercise can affect post-SCI remodeling of the brain function, through generation of systemic changes, such as improving blood circulation and neuroendocrine regulation and reducing spasticity [15]. Studies have confirmed that in animals with passive exercise training after spinal cord transection injury, the plasticity related neurotrophic factor, adenylate cyclase type 1 (ADCY1), and brain-derived neurotrophic factor (BNDF) increase in the somatosensory cortex, at levels significantly higher than in animals without training [16].…”
Section: Effect Of Exercise Training On Cerebral Cortexmentioning
confidence: 99%
“…Given that alternative physical therapies have been shown to reduce hypertonia, for example passive cycling with and without functional electrical stimulation (Kakebeeke et al, 2005, Krause et al, 2008, Rayegani et al, 2011), we hypothesized that RAST would similarly have a positive effect on reducing hypertonia. One preliminary study found that a single session of RAST could yield a significant reduction in joint stiffness in children with spastic cerebral palsy (Schmartz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%